Reinfusion of peritoneal fluid elevates the level of plasma D‐dimer in patients with early‐onset ovarian hyperstimulation syndrome - Shiori Kumazawa; Kazuki Saito; Nanako Hashido; Rinko Ibi; Tomonori Ishikawa; Akira Wakabayashi; Naoyuki Miyasaka (Reproductive Medicine and Biology)
Abstract Purpose This study aimed to elucidate the factors that affect the dynamics of blood D‐dimer in ovarian hyperstimulation syndrome (OHSS). Methods We retrospectively reviewed medical records from two hospitals and extracted data obtained during assisted reproductive technology and OHSS treatment. Blood D‐dimer levels during hospitalization were plotted against body weight. Other factors possibly related to blood D‐dimer levels were also analyzed. Results The analysis included 10 patients with OHSS admitted between January 2013 and June 2023. In all patients, blood D‐dimer levels increased significantly when they convalesced from OHSS and lost weight. None of the patients showed clinical signs of thrombosis, which was confirmed using imaging tests in 8 of 10 patients. Two patients underwent cell‐free and concentrated ascites reinfusion therapy (CART), and their blood D‐dimer levels increased dramatically after the procedure. Conclusion Weight change and CART are associated with blood D‐dimer dynamics in OHSS. Our results show that elevated blood D‐dimer levels in patients with OHSS do not always represent the presence of thrombosis. Reinfusion of pooled D‐dimer in ascites may explain the D‐dimer surge during the recovery phase or after CART in these patients. Our study provides new perspectives on the clinical implications of D‐dimer during OHSS.